A new heterogeneous photocatalyst based on Wells–Dawson polyoxometalate and nickel coordination compounds: synthesis, structure and property1. Issue 30 (3rd April 2015) - Zhang, Lei; Shan, Bingqian; Yang, Hongxun; Wu, Dongshuang; Zhu, Rui; Nie, Jianhang; Cao, Rong
<x xml:space="preserve">Abstract</x> A new heterogeneous photocatalyst based on Wells–Dawson polyoxotungstates and nickel coordination compounds exhibits two broad band centered at 513 nm and 770 nm, extending induced light to visible region.